Detailed investigation of flameless oxidation of pulverized coal at pilot-scale (230 kWth). (5th January 2015) - Weidmann, M.; Verbaere, V.; Boutin, G.; Honoré, D.; Grathwohl, S.; Goddard, G.; Gobin, C.; Dieter, H.; Kneer, R.; Scheffknecht, G.
Abstract: Within this paper the detailed investigation of flameless oxidation (FLOX ® ) at the pilot-scale test facility at University of Stuttgart is presented. The experimental boundary conditions of two FLOX cases are given. Subsequently, the results obtained with OH* chemiluminescence imaging, velocity measurements and in-flame measurements of gas temperature and gas concentrations are described and interrelated. These clearly show the major features of FLOX e.g. delayed ignition, low reaction intensity as well as homogeneous temperature and radiation profiles. The root causes involved in the formation and reduction of nitric oxides are pointed out, e.g. the NO x precursors and the oxygen concentrations. Special focus is drawn on the influence of the coal carrier gases air or CO2 . Highlights: Related measurements of gas concentration, gas temperature and velocity of pulverized coal flameless oxidation. Identification of reaction zone topology by OH* chemiluminescence. Characterization of the formation and consumption of nitrogenous compounds by FTIR. Investigation of the use of CO2 as coal carrier gas.